CARACTERISTICILE SPECIFICE COMUNITĂŢILOR RURALE DIN MUNŢII APUSENI (PANGEEA, 2025)
In this paper we aim to highlight some of the features that are found in rural area in the Apuseni Mountains. Apuseni Mountains was declared as "disadvantaged area" due to the closure of mines, employing most people in the area. Effects consist of depopulation and aging. Urgent action is needed from the government, to save from extinction rural communities in the area.